POLITIK DAN PERUBAHAN PARADIGMA PENAFSIRAN AYAT-AYAT ALQURAN DALAM PROSES PILKADA DKI JAKARTA - Kaltsum, Lilik Ummi (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
The Quranic verse which is believed has multi-interpretation and can be understood from many aspects of sciences frequently brings people who did not have any competency in this field interpreting it based on their own desire and purpose to win a specific group from another. The phenomenon of interpreting some of the Qur?anic verses by some groups in the process of a gubernatorial election in DKI Jakarta produces different interpretations. Finally, this differences cause conflict and debate which cannot be avoided. Every groups assume their interpretation is absolute. As a result, they blame or infidel another group. This research examines the interpretations of the Qur?anic verses which are used during a gubernatorial election in DKI Jakarta. The object of this study based on texts and audio which are spread on the sites of the internet. All of the data will be interpreted based on the theory of interpretation rules approach. This research concludes that the personal or group interest is able to change the paradigm of the Qur?anic interpretation including political interest.